2014
DOI: 10.1111/jen.12125
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of commercial formulations of entomopathogenic nematodes against tropical sod webworm, Herpetogramma phaeopteralis (Lepidoptera: Crambidae)

Abstract: Large quantities of insecticides are used on warm season turfgrasses to combat pest infestations. To investigate the potential for microbial control, we screened commercially available entomopathogenic nematode products against Herpetogramma phaeopteralis Guen ee, an economically injurious pest in the south-eastern United States and Caribbean islands. All tested products, based on Steinernema carpocapsae, S. feltiae, Heterorhabditis bacteriophora, H. megidis and H. indica, were pathogenic to H. phaeopteralis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Por su parte, Tofangsazi et al (2014) reportan que la DL50 de Heterorhabditis indica, H. bacteriophora y H. megidis en suspensión para el control de larvas pequeñas de Herpetogramma phaeopteralis fue de 387, 270 y 554 (JI.ml -1 ) por larva. Mahmoud (2014) reportaron que la DL50 de H. bacteriophora sobre larvas de los olivos Palpita unionalis a 25°C fue de 38,2 (30,9-47,2) JI.larva -1 .…”
Section: Determinación De La Dl50unclassified
“…Por su parte, Tofangsazi et al (2014) reportan que la DL50 de Heterorhabditis indica, H. bacteriophora y H. megidis en suspensión para el control de larvas pequeñas de Herpetogramma phaeopteralis fue de 387, 270 y 554 (JI.ml -1 ) por larva. Mahmoud (2014) reportaron que la DL50 de H. bacteriophora sobre larvas de los olivos Palpita unionalis a 25°C fue de 38,2 (30,9-47,2) JI.larva -1 .…”
Section: Determinación De La Dl50unclassified
“…These observations indicated two types of variability related to virulence of EPNs viz., variability among EPN species and variability due to insect host. Earlier Tofangsazi et al, (2014) studied the effect of commercial formulations of five EPN species against TSW and reported variability in virulence among five EPN species against TSW.…”
Section: Behaviour and Foraging Of Infective Juveniles Of Epnmentioning
confidence: 99%
“…Previously, Tofangsazi et al, (2014) demonstrated that S. carpocapsae caused the highest mortality in comparison to S. feltiae, H. bacteriophora, H. megidis and H. indica against TSW, using their commercial formulations. Studies have also established the efficacy and applicability of EPNs against other insect pests of turfgrass.…”
Section: Field Evaluation Of Epn Against Tswmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to develop environmentally friendly alternatives to control soil pests, such as entomopathogenic nematodes (EPNs). The EPNs of the families Heterorhabditidae and Steinernematidae are obligate parasites of insects and have demonstrated to pose a high potential for the agricultural pest control (Ehlers 1996;Georgis et al 2006;Lacey & Shapiro-Ilan 2008;San-Blas 2013;Tofangsazi et al 2014;van Zyl & Malan 2014;Půža 2015). Also, they have been exempted from registration in the USA, are compatible with many chemical pesticides and amenable to genetic selection (Kaya & Gaugler 1993).…”
mentioning
confidence: 99%